Clinical features of familial hypercholesterolemia in Korea: Predictors of pathogenic mutations and coronary artery disease – A study supported by the Korean Society of Lipidology and Atherosclerosis. Issue 1 (November 2015) - Shin, Dong Geum; Han, Soo Min; Kim, Doo Il; Rhee, Moo-Yong; Lee, Byoung-Kwon; Ahn, Young Keun; Cho, Byung Ryul; Woo, Jeong-Taek; Hur, Seung-Ho; Jeong, Jin-Ok; Jang, Yangsoo; Lee, Ji Hyun; et al.
Abstract: Background: Proper screening and diagnosis of familial hypercholesterolemia (FH) is of critical importance for cardiovascular prevention. However, the clinical diagnosis of FH remains difficult partly because its phenotype can vary between different ethnicities. The aim of this study was to determine the clinical features and the best diagnostic approach in Korean FH patients. The predictors of putative pathogenic mutations and coronary artery disease (CAD) were also identified. Methods and Results: Ninety-seven patients with low-density lipoprotein-cholesterol >190 mg/dL and xanthoma or FH-compatible family history were included. Putative pathogenic mutations in LDLR, APOB, or PCSK9 genes were identified in 32% of the enrolled patients. The subjects were classified according to four sets of clinical criteria (Simon Broome, Dutch, MEDPED, Japanese). The mutation rates in definite type FH of Simon Broome or Dutch criteria were 35%–37% and lower in our patients than in those of other countries. The mutation detection rate by MEDPED criteria was 67%–75% and higher than those based on other criteria. The best low-density lipoprotein-cholesterol (LDL-C) threshold for predicting mutations was 225 mg/dL. LDL-C was found to be the only independent predictor of mutation carriers, while hypertension and low high-density lipoprotein-cholesterol were predictive of CAD. Conclusions: The conventional clinical criteria showed limited mutation detection power and low specificities in Korean FH patients, in whom the best LDL-C threshold for putative mutation was 225 mg/dL. Traditional cardiovascular risk factors were also significantly associated with CAD risk in this population. Abstract : Putative pathogenic mutations of 3 FH genes were in 32% of suspected FH patients. The specificities of conventional diagnostic criteria were low in Korean FHs. The best LDL-C threshold for mutations was 225 mg/dL. LDL-C predicted mutations, while hypertension and low HDL-C predicted CAD.